2015
DOI: 10.1371/journal.pone.0144774
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection Compared with Gastrectomy to Treat Early Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundEndoscopic resection and gastrectomy are treatment modalities for early gastric cancer, but their relative benefits and risks are unclear. We conducted a systematic review and meta-analysis to compare endoscopic resection and gastrectomy for treating early gastric cancer.MethodsWe searched PubMed, Embase, and the Cochrane Library until April 2015 for studies comparing endoscopic resection with gastrectomy for treatment of early gastric cancer. Outcome measures were five-year overall survival (OS), le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…[2] Surgical resection is a conventional treatment for EGC and endoscopic resection was considered an alternative treatment method for surgical resection only for elderly patients and cancer of the upper stomach. [3,4] However, endoscopic resection is widely used for EGC as the proportion of EGC among stomach cancers has increased with the widespread use of screening endoscopy. [1,3] As the stomach is preserved after endoscopic resection, the chance of metachronous stomach cancer is higher than that after surgical resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Surgical resection is a conventional treatment for EGC and endoscopic resection was considered an alternative treatment method for surgical resection only for elderly patients and cancer of the upper stomach. [3,4] However, endoscopic resection is widely used for EGC as the proportion of EGC among stomach cancers has increased with the widespread use of screening endoscopy. [1,3] As the stomach is preserved after endoscopic resection, the chance of metachronous stomach cancer is higher than that after surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] However, endoscopic resection is widely used for EGC as the proportion of EGC among stomach cancers has increased with the widespread use of screening endoscopy. [1,3] As the stomach is preserved after endoscopic resection, the chance of metachronous stomach cancer is higher than that after surgical resection. However, repeated endoscopic resection is possible.…”
Section: Introductionmentioning
confidence: 99%
“…44 Additionally, as endoscopic resection is associated with less morbidity, fewer procedure-related adverse events, and fewer complications, ESD could be used as the standard treatment for early gastric cancer. 47,48 The Western perspective on endoscopic submucosal dissection for gastric cancer Since the prevalence of gastric cancer in Western countries is significantly lower than in Japan and Korea, local data and experience Estimating the depth of invasion is mandatory Based on information from the Japanese Gastric Cancer Association, reference 9.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the impossibility of regional lymph nodes removed during the ESD procedure is another major limitation, which may probably result in tumor recurrence and the invasive radical gastrectomy. Previous systematic review and meta-analysis revealed that the 5-year DFS survival rate may not be different between the endoscopic resection and surgery in the treatment of EGC as well [ 6 ].…”
Section: Introductionmentioning
confidence: 99%